Radiosonde observations of gravity waves in the lower stratosphere over Davis, Antarctica - Murphy, DJ; Alexander, SP; Klekociuk, AR; Love, PT; Vincent, RA (Journal of Geophysical Research: Atmospheres, 2014)
Radiosonde observations made from Davis station, Antarctica, (68.6S, 78.0E) between 2001 and 2012 are used to compile a climatology of lower stratosphere inertial gravity wave characteristics. Wavelet analysis extracts single wave packets from the wind and temperature perturbations. Wavelet parameters, combined with linear gravity wave theory, allow for the derivation of a wide range of wave characteristics. Observational filtering associated with this analysis preferentially selects inertial gravity waves with vertical wavelengths less than 23 km. The vertical propagation statistics show strong temporal and height variations. The waves propagate close to the horizontal and are strongly advected by the background wind in the wintertime. Notably, around half of the waves observed in the stratosphere above Davis between early May and mid-October propagate downward. This feature is distributed over the observed stratospheric height range. Based on the similarity between the upward and downward propagating waves and on the vertical structure of the nonlinear balance residual in the polar winter stratosphere, it is concluded that a source due to imbalanced flow that is distributed across the winter lower stratosphere best explains the observations. Calculations of kinetic and potential energies and momentum fluxes highlight the potential for variations in results due to different analysis techniques.